Manual of 3D Echocardiography - Casas Rojo, Eduardo; Fernandez-Golfin, Covadonga; Zamorano, José Luis (Springer International Publishing : Imprint: Springer, 2017)
This book is a practical manual to explain critical clinical practice in three-dimensional (3D) echocardiography. The use of this technology has been limited to certain pioneer imaging units, but with the advent of lower cost hardware it is spreading and reaching more users that will start to use it often without previous experience or formal academic training. Manual of 3D Echocardiography provides readers with a full review of the features, clinical indications and methodological aspects of 3D echo in a practical and methodical way. These techniques are becoming more diverse, as they are applied to transthoracic and transesophageal studies, 3D-wall motion tracking, fusion of echocardiographic and fluoroscopy navigation, fusion of wall motion tracking and coronary tomography. All these aspects are described and explained deeply in this book and hence this will be of value for all training in or who want to understand better the technique and how to apply it.
Keywords: Medicine.; Cardiac imaging.; Cardiology.; elektronické knihy; electronic books